Development of HOTS-Based Interactive E-Modules to Train High School Students' Critical Thinking Skills on Harmonic Vibration Material - Muhammad Akbar Agustian; Afrizal Mayub; Dedy Hamdani (CV. Media Inti Teknologi, 2024)
The goal of this project is to create an interactive e-module using Hots to teach high school students how to think critically about content related to harmonic vibration that is both realistic and well-received by the students. Thirty-five pupils from class X SMAN 01 Bengkulu City provided the data for this study. The 4D model research method—which stands for Define, Design, Develop, and Disseminate—is used in this study. The study employed many instruments, including observation sheets, student impression sheets, instructor needs questionnaires, and expert team validation sheets. In order to aid students in understanding the teaching materials, the resulting e-module includes text, tables, graphics, formulas, and learning videos. Additionally, an interactive quiz within the e-module allows students to practice their skills. The results of this study indicate that the developed e-module is included in the very feasible category with a value of 87.2%. Students' perception of this e-module is included in the very good category with a value of 84.4%.